Doing More With Less: Review of Dolutegravir-Lamivudine, a Novel Single-Tablet Regimen for Antiretroviral-Naïve Adults With HIV-1 Infection. Issue 12 (December 2020) - Santevecchi, Barbara A.; Miller, Stacy; Childs-Kean, Lindsey M.
Objective: To review data on efficacy and safety of dolutegravir (DTG) and lamivudine (3TC) in treatment-naïve adults with HIV-1 infection. Data Sources: Phase III clinical trials and review articles were identified through PubMed (1996 to March 2020) and ClinicalTrials.gov (2000 to May 2020) using the keywords dolutegravir, lamivudine, and HIV . Study Selection and Data Extraction: Relevant clinical trials and review articles available in English evaluating efficacy and safety of DTG and 3TC were included. Data Synthesis: The once-daily, single-tablet regimen of DTG/3TC is the first dual antiretroviral therapy (ART) recommended for initial therapy in treatment-naïve adults with HIV-1 infection. DTG and 3TC were compared with a regimen of DTG and tenofovir disoproxil fumarate/emtricitabine in the GEMINI studies and demonstrated noninferiority for the primary end point of virological suppression at up to 96 weeks. No treatment-emergent resistance mutations were identified in a small group of participants who did not reach virological suppression. The regimen is well tolerated, and the most common adverse events reported in trials include headache, diarrhea, nausea, insomnia, and fatigue. Relevance to Patient Care and Clinical Practice: This dual-ART regimen is a favorable treatment option for ART-naïve patients with HIV-1 RNA <500 000 copies/mL, absence of hepatitis B virus, and no resistance to DTG or 3TC. Benefits of dual ART include reduction in treatment-related adverse events and toxicities, drug interactions, and cost. In addition, the once-daily, single-tablet formulation promotes adherence. Conclusions: DTG/3TC has demonstrated efficacy in maintaining virological suppression in ART-naïve patients at up to 96 weeks while minimizing treatment-related adverse events and toxicities.